Biochar amendment alters root morphology of maize plant: Its implications in enhancing nutrient uptake and shoot growth under reduced irrigation regimes - Wan, Heng; Liu, Xuezhi; Shi, Qimiao; Chen, Yiting; Jiang, Miao; Zhang, Jiarui; Cui, Bingjing; Hou, Jingxiang; Wei, Zhenhua; Hossain, Mohammad Anwar; Liu, Fulai (Frontiers in Plant Science, 2023)
Biochar amendment provides multiple benefits in enhancing crop productivity and soil nutrient availability. However, whether biochar addition affects root morphology and alters plant nutrient uptake and shoot growth under different irrigation regimes remain largely unknown. A split-root pot experiment with maize (Zea mays L.) was conducted on clay loam soil mixed with 2% (w/w) of wheat-straw (WSP) and softwood (SWP) biochar. The plants were subjected to full (FI), deficit (DI) and alternate partial root-zone drying (PRD) irrigation from the fourth leaf to the grain-filling stage. The results showed that, compared to plants grown in unamended soils, plants grown in the biochar-amended soils possessed greater total root length, area, diameter, volume, tips, forks, crossings and root length density, and which were further amplified by PRD. Despite a negative effect on soil available phosphorus (P)-pool, WSP addition improved soil available nitrogen (N)-, potassium (K)-, calcium (Ca)-pool and cation exchange capacity under reduced irrigation. Even though biochar negatively affected nutrient concentrations in shoots as exemplified by lowered N, P, K (except leaf), and Ca concentration, it dramatically enhanced plant total N, P, K, Ca uptake and biomass. Principal component analysis (PCA) revealed that the modified root morphology and increased soil available nutrients-pools, and consequently the higher plant total nutrients uptake might have facilitated the enhanced shoot growth and yeild of maize plants in biochar-added soils. Biochar amendment further lowered specific leaf area while increased leaf N concentration per area to root N concentration per length ratio. All these effects were evident upon WSP amendment. Moreover, PRD outperformed DI in increasing root area to leaf area ratio. Overall, these findings suggest that WSP combined with PRD could be a promising strategy to improve the growth and nutrients uptake of maize plants.